Evaluating the effectiveness of web-based oral health education on enhancing mothers' awareness: a semi-experimental internet-based intervention - Kasra Kashani; Arash Shahravan; Afshin Sarafinejad (BMC, 2024)
Abstract Objectives This study examined the impact of web-based education on enhancing mothers' awareness of oral health care for children aged 9 and 12 years. It focused on the crucial role of mothers in educating about oral health to prevent dental diseases and reduce long-term healthcare costs. Methods Mothers were divided into three groups: control, intervention with a web system, and intervention with a brochure. Over one month, their knowledge about their children's oral health was assessed before and after the intervention. Results Data were analyzed using parametric t-tests and non-parametric Mann-Whitney U tests. The findings indicated a significant increase in parental awareness in both intervention groups. Conclusion It is recommended that parent education be done using web-based systems or mobile apps, which are better choices due to greater accessibility and interactivity.